Effectiveness of Psychospiritual Awareness Training and Butterfly Hug Technique on Emotional Regulation of Grade VI Elementary School - Muhammad Adfan Madji; Nasywa Nabillah; Lusiana Dwi Puspita; Nabilla Rosydah; Magita Salsabilla; Herliyana Isnaeni (Marlajar: Journal of Science, Technology, and Innovation, 2026)
Social changes and academic demands on final-year elementary school students often trigger emotional challenges that are not balanced with adequate mental health assistance. This study aims to examine the effectiveness of the training program "Petualangan Mengenal Diri, Aku Hebat, Aku Bangga" (Adventure of Self-Discovery, I am Great, I am Proud) which integrates a psychospiritual awareness approach and the Butterfly Hug technique to enhance self-awareness and emotional regulation among students. Utilizing a quasi-experimental design with a One-Group Pretest-Posttest Design, this study involved 20 sixth-grade students from SDN Bluru Kidul 1 Sidoarjo as experimental subjects selected through a purposive sampling technique. Quantitative data were collected through written cognitive tests, while qualitative data were gathered through behavioral observations and expression reflection sheets. The results of the descriptive statistical analysis showed a significant surge in cognitive understanding, where the students' average score increased from 91 in the pre-test to 98 in the post-test. Furthermore, 18 students achieved perfect scores, and the lowest score in the class was elevated from 40 to 80. Qualitatively, this intervention proved to provide a safe space for students to express their emotions, reduce anxiety independently, and foster a growth mindset. This study concludes that the combination of psychospiritual intervention and practical clinical techniques is effectively used as an initial psychological assistance model to optimize students' mental readiness in facing developmental transitional phases